Adverse events with risankizumab in the real world: postmarketing pharmacovigilance assessment of the FDA adverse event reporting system - Shu, Yamin; Chen, Jing; Ding, Yiling; Zhang, Qilin (Frontiers in Immunology, 2023)
Background: Risankizumab, a humanized IgG1 monoclonal antibody that selectively inhibits IL-23, is currently approved for the treatment of moderate-to-severe plaque psoriasis and Crohn's disease. The real-world safety study of risankizumab in large sample population are currently lacking. The aim of this study was to evaluate risankizumab-associated adverse events (AEs) and characterise the clinical priority through data mining of FDA Adverse Event Reporting System (FAERS). Methods: Disproportionality analyses were performed by calculating the reporting odds ratios (ROR), deemed significant when the lower limit of the 95% confidence interval was greater than 1, to quantify the signals of risankizumab-related AEs from the second quarter (Q2) of 2019 to 2022 Q3. Serious and non-serious cases were compared, and signals were prioritized using a rating scale. Results: Risankizumab was recorded in 10,235 reports, with 161 AEs associated with significant disproportionality. Of note, 37 PTs in at least 30 cases were classified as unexpected AEs, which were uncovered in the drug label, such as myocardial infarction, cataract, pancreatitis, diabetes mellitus, stress and nephrolithiasis. 74.68%, 25.32%% and 0% PTs were graded as weak, moderate and strong clinical priorities, respectively. 48 risankizumab-related AEs such as pneumonia, cerebrovascular accident, cataract, loss of consciousness, cardiac disorder, hepatic cirrhosis, thrombosis, etc, were more likely to be reported as serious AEs. The median TTO of moderate and weak signals related to risankizumab was 115 (IQR 16.75-305) and 124 (IQR 29-301) days, respectively. All of the disproportionality signals had early failure type features, indicating that risankizumab-associated AEs gradually decreased over time. Conclusion: Our study found potential new AE signals and provided valuable evidence for clinicians to mitigate the risk of risankizumab-associated AEs based on an extensive analysis of a large-scale post-marketing international safety database.